Gait Measures as Predictors of Poststroke Cognitive Function. Issue 4 (April 2015) - Ben Assayag, Einor; Shenhar-Tsarfaty, Shani; Korczyn, Amos D.; Kliper, Efrat; Hallevi, Hen; Shopin, Ludmila; Auriel, Eitan; Giladi, Nir; Mike, Anat; Halevy, Anat; Weiss, Aner; Mirelman, Anat; et al.
<x xml:space="preserve">Abstract</x> Background and Purpose— Patients with stroke are at risk for developing cognitive impairment. We tested whether the assessment of balance and gait can enhance the prediction of long-term cognitive outcome in stroke survivors. Methods— Participants were patients with first-ever, mild-moderate ischemic stroke or transient ischemic attack from the Tel Aviv Brain Acute Stroke Cohort (TABASCO) study, a large prospective cohort study, who underwent 3-T MRI and were followed for ≥2 years using neurological, neuropsychological, and mobility examinations 6, 12, and 24 months after the index event. Results— Data were available for 298 patients (age: 66.7±9.6 years). Forty-six participants (15.4%) developed cognitive decline (CD) over the 2 years of follow-up. The CD group and cognitively intact group did not differ in their neurological deficits or in their infarct volume or location. Nonetheless, 6 months after stroke, the Timed Up and Go test took longer in those who later developed CD (P<0.001). Additionally, the CD group also had lower Berg Balance Scale scores (P<0.001), slower gait (P<0.001), and fewer correct answers during dual-task walking (P=0.006). Separate analyses of the patients with transient ischemic attack revealed similar results. Multivariate regression analysis showed that Timed Up and Go times >12 s at 6 months after stroke/transient ischemic attack was a significant independent risk marker of CD 24 months after stroke (odds ratio=6.07, 95% confidence interval: 1.36–27.15). Conclusions— These results suggest that measures of balance and gait are significant risk markers of cognitive status 2 years after stroke. Relatively simple, performance-based tests of mobility may enhance the identification of stroke/transient ischemic attack survivors who have an increased risk of developing CD. Clinical Trial Registration— URL: http://www.clinicaltrials.gov. Unique identifier: NCT01926691.